2003
DOI: 10.1213/01.ane.0000062522.21048.61
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study of Emergence Agitation in the Pediatric Postanesthesia Care Unit

Abstract: Children may become agitated after general anesthesia. This study describes several factors that may increase the risk for agitation. These data are important in planning anesthesia care for young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
381
2
18

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 416 publications
(418 citation statements)
references
References 40 publications
17
381
2
18
Order By: Relevance
“…24 Early epidemiologic studies reported widely varying incidences of EA in children, ranging from 10-80%. 25,26 Although the precise etiology of EA is currently unknown, suggested risk factors include pain, preschool age, the type of otolaryngologic or ophthalmologic procedure performed, and the use of sevoflurane or desflurane. 25,26 It has been reported that the incidence of POV in children is twice as high as in adults, and age [ 3 yr has been proposed as an independent risk factor for POV.…”
Section: Discussionmentioning
confidence: 99%
“…24 Early epidemiologic studies reported widely varying incidences of EA in children, ranging from 10-80%. 25,26 Although the precise etiology of EA is currently unknown, suggested risk factors include pain, preschool age, the type of otolaryngologic or ophthalmologic procedure performed, and the use of sevoflurane or desflurane. 25,26 It has been reported that the incidence of POV in children is twice as high as in adults, and age [ 3 yr has been proposed as an independent risk factor for POV.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that strabismus surgery in children is complicated by a high incidence of emergence agitation (EA). 2 It has also been well established that propofol-based anesthetic techniques and/or techniques that include low doses of opioids or sedative hypnotics can significantly decrease the incidence of EA. 3 In their study, Chen et al evaluated outcomes in children undergoing eye muscle surgery who received no propofol, sedatives, or parenteral analgesics during the study period.…”
Section: To the Editormentioning
confidence: 99%
“…5,11 When children are separated from their parents and sent to the operating room alone, this is traumatic and increases the risk of emergence agitation. 12 Experimental research has demonstrated that separating mother rats from their young during the preoperative period triggered postoperative agitation.…”
Section: Psychological Social and Environmental Factors Related To Tmentioning
confidence: 99%
“…11,20 It is speculated that the sensation of suffocation in otorhinolaryngological procedures may be responsible for these events; although scientific evidence indicating that this is a causative factor of agitation is scarce and inconsistent.…”
Section: Type Of Surgerymentioning
confidence: 99%
See 1 more Smart Citation